Hubungan Karakteristik Individu, Konsentrasi Benzena dengan Degenerasi DNA Pada Pekerja Pengecatan Mobil - Heningdia Pastika Asih; Abdul Rohim Tualeka (Media Gizi Kesmas, 2022)
Background: A car paint shop is one of the works that use paint as the main working material containing benzene. Benzene is a colorless liquid aromatic compound that is carcinogenic to humans. This compound is classified as a group 1 human carcinogen by the IARC (International Agency for Research on Cancer). Objectives: This study aimed to analyze the correlation between individual characteristics and workplace benzene concentrations with DNA degeneration of workers in an automotive paint shop in Kalijudan, Surabaya. Methods: This study is an observational study with a cross-sectional design and a quantitative approach. Secondary data from the previous study were collected from 20 respondents, all of whom were paint workers in an auto paint shop. The dependent variable in this study is DNA degeneration and the independent variables are age, body mass index (BMI), number of years working, smoking behavior, and benzene concentration. To analyze the correlation of independent and dependent variables, the chi-square test was used. And then the phi test and Cramer's v are used to analyze the strength of the correlation between the two variables. Results: Measurements of benzene concentrations in the workplace showed higher mean concentrations than TLV-TWA. As a result of laboratory tests, 13 out of 20 workers showed DNA degeneration. At the same time, the results showed a moderate correlation between BMI and DNA degeneration, and a very weak correlation between benzene concentration at work, individual characteristics (worker age, years of work, and smoking behavior) and DNA degeneration. Conclusions: This study found no correlation between individual characteristics and workplace benzene concentration with DNA degeneration in Surabaya auto paint shop workers. Keywords: benzene, car painting shop, DNA, individual characteristics